Folk heritage collections in crisis - Danielson, Virginia; Cohen, Elizabeth; Seeger, Anthony (Council on Library and Information Resources, 2001)
In December 2000, a group of folklorists, sound engineers, preservation experts, lawyers, librarians, and archivists met to discuss what would be needed to ensure the long-term accessibility of folk heritage sound collections. The American Folklore Society and the American Folklife Center at the Library of Congress convened the meeting, with support from CLIR, National Endowment for the Arts, and National Endowment for the Humanities. This report includes the text of the three keynote presentations. A list of 27 recommendations for access, preservation, and rights management is presented, as well as responses to the presentations and summaries of the discussions.